2019
DOI: 10.1186/s12885-019-5681-6
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic modeling of personalized drug combinations from integrated chemical screen and molecular data in sarcoma

Abstract: Background Cancer patients with advanced disease routinely exhaust available clinical regimens and lack actionable genomic medicine results, leaving a large patient population without effective treatments options when their disease inevitably progresses. To address the unmet clinical need for evidence-based therapy assignment when standard clinical approaches have failed, we have developed a probabilistic computational modeling approach which integrates molecular sequencing data with functional as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Likewise, genomic analyses in combination with screening cancer cell lines against libraries of drugs have the potential to improve the correlation between genomic biomarkers and response to therapy. Such an approach has been used to identify biomarkers for response to therapy of several sarcomas using cell lines, patient‐derived samples, and canine sarcoma as proof of principle (Berlow et al , 2019). This approach is challenging for studying sarcoma, due to the limited number of cell lines available, although isolation of new cell lines (Salawu et al , 2016) and sarcoma PDX models is improving (Stebbing et al , 2014).…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…Likewise, genomic analyses in combination with screening cancer cell lines against libraries of drugs have the potential to improve the correlation between genomic biomarkers and response to therapy. Such an approach has been used to identify biomarkers for response to therapy of several sarcomas using cell lines, patient‐derived samples, and canine sarcoma as proof of principle (Berlow et al , 2019). This approach is challenging for studying sarcoma, due to the limited number of cell lines available, although isolation of new cell lines (Salawu et al , 2016) and sarcoma PDX models is improving (Stebbing et al , 2014).…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…This system could help more patients benefit from precision therapy. 154 Surprisingly, another group developed an in silico prediction system that identifies new combinations, which solved another problem of combination therapy, finding new combinations. 155 With the help of machine learning and artificial intelligence, drug combinations containing sorafenib could benefit more HCC patients.…”
Section: Perspectivesmentioning
confidence: 99%
“…Combinations of drugs that have a specific targeting profile in different signalling pathways at lower doses will demonstrate a better safety profile, and are easier to adapt in a personalised fashion. 60 Previous studies have shown the importance of combining drugs that interfere with molecules up- [61][62][63] and downstream [64][65][66] of a certain signalling cascade. However, the choice of targets and drugs is crucial and determines treatment success.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of drugs that have a specific targeting profile in different signalling pathways at lower doses will demonstrate a better safety profile, and are easier to adapt in a personalised fashion. 60 …”
Section: Discussionmentioning
confidence: 99%